Delphi consensus recommendations on how to provide cardiovascular rehabilitation in the COVID-19 era - Ambrosetti, Marco (2021)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author(s) 2020. For permissions, please email: journals.permissions@oup.com.